A importância das áreas verdes urbanas na promoção dos serviços ecossistêmicos na cidade de Santa Rita/PB - Macieira, Milca Laís da Luz (2024)
To reduce vulnerability and enhance the resilience of urban settlements, specific adaptations must be made in cities, including the creation and/or maintenance of green areas that serve social and ecological functions. Therefore, the present study focuses on Santa Rita, a city located in the metropolitan region of João Pessoa/PB, aiming to investigate the importance of urban green spaces in promoting ecosystem services for the city's population. Initially, a literature review was conducted based on the topics addressed in the study. During the diagnostic phase, a field sheet was used to gather information considering conservation status and environmental characteristics. Additionally, Geographic Information System (GIS) was employed for data processing. Sample space definition was guided by research criteria, population involvement, and availability of microclimate monitoring equipment. Ecosystem services were classified according to the Common International Classification of Ecosystem Services (CICES) into provisioning, cultural, and regulating services. Provisioning services were identified through secondary sources and onsite surveys of flora in sampled areas. Cultural services were assessed based on the municipality's cultural calendar and systematic on-site monitoring of activities in sampled areas. For regulating services, temperature and relative humidity conditions were monitored in two selected areas during the transition between seasons, characterized by the Thermal Discomfort Index (TDI). Data collection also involved direct contact with park users and passersby using a structured form, with subsequent statistical and descriptive analysis. Results indicated that out of 44 evaluated squares, only 10 maintained good conservation of natural and built elements during the study period. Regarding microclimate regulation services, clearer benefits were observed in the morning cycle, notably with lower temperatures in Dom Pedro II Square (P2), approximately 6.8°C cooler than Povo Square (P1), attributed to vegetative cover. Among the sampled squares, at least three are capable of or already provide food production services with fruit-bearing species and show potential for medicinal plants. In terms of cultural ecosystem services, all sampled squares host events and sustain various functions. Overall, the study concludes that despite technical limitations, it significantly deepened understanding of the diverse ecosystem services that squares can offer. Consequently, it is hoped that these findings will guide practical interventions aimed at improving environmental quality and enhancing the well-being of the urban population in Santa Rita.